2018
DOI: 10.1186/s13089-018-0112-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of abdominal point of care ultrasound performed by an emergency physician in acute right iliac fossa pain

Abstract: BackgroundRight iliac fossa abdominal pain is a common reason for emergency ward admissions, its etiology is difficult to diagnose. It can be facilitated by an imaging examination, such as a Computerized Tomography scan which exposes the patient to ionizing radiation and implies delays. A bedside ultrasound performed by emergency physicians could avoid these issues. The aim of our study was to assess the performance of ultrasound carried out at the patient’s bedside by an emergency physician compared with a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Nowadays, the abdominal pain workup in the ED is based on a combination of clinical assessment and point-of-care ultrasound (POCUS), aiming to increase diagnostic accuracy and to reduce the time to diagnosis, ED length of stay and the number of computed tomography (CT) scan requests [3,4]. In specific conditions, such as suspected abdominal aortic aneurysm, biliary and renal pathologies, pregnancy-related disorders and appendicitis, there are consolidated protocols that imply the systematic use of POCUS as an initial screening tool [5][6][7][8][9][10][11]. Previous literature has investigated the role of standard ultrasound in diverticulitis [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the abdominal pain workup in the ED is based on a combination of clinical assessment and point-of-care ultrasound (POCUS), aiming to increase diagnostic accuracy and to reduce the time to diagnosis, ED length of stay and the number of computed tomography (CT) scan requests [3,4]. In specific conditions, such as suspected abdominal aortic aneurysm, biliary and renal pathologies, pregnancy-related disorders and appendicitis, there are consolidated protocols that imply the systematic use of POCUS as an initial screening tool [5][6][7][8][9][10][11]. Previous literature has investigated the role of standard ultrasound in diverticulitis [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Bourcier, et al ( 2018) 11 conducted a study with abdominal pain patients. They showed the diagnosed cases were: appendicitis (53), non-specific abdominal pain (48), lymphadenitis (22), ileitis (11), complicated ovarian cysts (7), neoplasias (5), inflammatory or infectious colitis (5), inguinal herniations (3), bowel obstructions (2), and salpingitis (2).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were identified using several of the above-mentioned techniques to help diagnose patients presenting with abdominal pain and found an overall improvement in diagnostic accuracy compared to work-up as usual [150, 151].…”
Section: Resultsmentioning
confidence: 99%